Како Кант ја избрка φρόνησις од етиката? - Поповска, Јасмина (Филозофско друштво на Македонија, 2025)
The great Kantian ethical “Copernican” revolution consists in repositioning ethics from the realm of the contingent, uncertain, and accidental into the sphere of the objective, rationally necessary, a priori, unconditional, and categorical. Everything that falls within the domain of the hypothetical, including the choice of means for achieving happiness or well-being, is, according to Kant, unnecessary and non-absolute, and is thus excluded from the realm of the ethical. As a result, in this system, there is no place for the key concept that had previously defined ethical thought: φρόνησις (practical wisdom). This concept no longer has an ethical function but instead represents a form of practical knowledge about selecting the means to achieve well-being—a goal that, according to Kant, is no longer a principle of morality. After Kant, φρόνησις becomes pure Klugheit or cleverness, meaning it is reduced to a practical skill of sharpness, ingenuity, foresight, or resourcefulness. Through Kant’s principle of duty and the categorical imperative, this text addresses several key ethical questions that become problematic with the rejection of φρόνησις. The focus is on the role of morality in achieving happiness or overall well-being in life.
Keywords: Kant, φρόνησις, categorical, hypothetical, well-being